3y+2.5x-3.7=0

Simple and best practice solution for 3y+2.5x-3.7=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+2.5x-3.7=0 equation:


Simplifying
3y + 2.5x + -3.7 = 0

Reorder the terms:
-3.7 + 2.5x + 3y = 0

Solving
-3.7 + 2.5x + 3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3.7' to each side of the equation.
-3.7 + 2.5x + 3.7 + 3y = 0 + 3.7

Reorder the terms:
-3.7 + 3.7 + 2.5x + 3y = 0 + 3.7

Combine like terms: -3.7 + 3.7 = 0.0
0.0 + 2.5x + 3y = 0 + 3.7
2.5x + 3y = 0 + 3.7

Combine like terms: 0 + 3.7 = 3.7
2.5x + 3y = 3.7

Add '-3y' to each side of the equation.
2.5x + 3y + -3y = 3.7 + -3y

Combine like terms: 3y + -3y = 0
2.5x + 0 = 3.7 + -3y
2.5x = 3.7 + -3y

Divide each side by '2.5'.
x = 1.48 + -1.2y

Simplifying
x = 1.48 + -1.2y

See similar equations:

| x=-22+-6w | | -110=2(1+8) | | 2y^2=-y+10 | | 4-5k-6=-4k-1 | | (6/7)x=24 | | 7x+4=5x-1 | | 2=f/2 | | -182=-6(7-6n)-n | | 4z^2-16+12=0 | | 7x+3/2-9x-8/4=6 | | -22-x=3w-w+4w | | 4/5x+4/3+2x | | 1/5x-y=76 | | -7p-(-7+5p)=-4(3p-7) | | 5(1+7)-5=175 | | x+4/15=-1 | | (7x^2-7x+8)+(9x^3-5x)= | | 3(x+3)+12=6x+3 | | 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 | | 4-6a+4a=-115(7-2a) | | 5x+47= | | 11/6x6/35 | | 4(2a-6)+8b= | | (3x+39/8)=0 | | 7k-2(3k+1)= | | 5x-1+x=15 | | 11=((7w-9)/2)+((8w+1)/5) | | y/8+4=6 |

Equations solver categories